MATH SOLVE

3 months ago

Q:
# Help me please???? Simplify completely.(c6c2)5

Accepted Solution

A:

Before we begin, you should remember the following exponential rules:Rule #1: xᵃ * xᵇ = xᵃ⁺ᵇRule #2: (xᵃ)ᵇ = xᵃᵇRule#3: xᵃ / xᵇ = xᵃ⁻ᵇNow, for the given problem:1- If the given problem was:(c⁶c²)⁵We will start by simplifying what's inside the brackets.To do this, we will apply Rule#1 as follows:(c⁶c²)⁵ = (c⁶⁺²)⁵ = (c⁸)⁵Now, we can simplify this by applying Rule#2 as follows:(c⁸)⁵ = c⁸ˣ⁵ = c⁴⁰2- If the given problem was:[tex](\frac{c^6}{c^2} )^5[/tex]We will start by simplifying what's inside the brackets.To do this, we will apply Rule#3 as follows:[tex](\frac{c^6}{c^2} )^5 = (c^6^-^2)^5 = (c^4)^5[/tex]Now, we can simplify this by applying Rule#2 as follows:(c⁴)⁵ = c⁴ˣ⁵ = c²⁰Hope this helps :)